2006
DOI: 10.1292/jvms.68.179
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Porcine Circovirus 1 and Circovirus 2 in Primary Porcine Hepatocyte and Kidney Cell Cultures

Abstract: ABSTRACT. Infectivity of porcine circovirus (PCV) 1 and PCV2 was examined in primary porcine hepatocyte culture by comparing that of PCV in primary kidney cell culture. The virus titer of PCV2-infected hepatocyte cultures was higher than that of the PCV1-infected hepatocyte cultures and the PCV-infected kidney cell cultures. The number of virus-positive cells was most abundant in PCV2-infected hepatocyte cultures as determined by immunohistochemistry and/or in situ hybridization. The results of our data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this study, a testis-derived epithelial-cell line (ST) was susceptible to PCV2 infection, showing that epithelial cells from other organs may also be susceptible to PCV2 infection. PCV2 infects epithelial cells in pigs experimentally infected with PCV2 (23), in PMWS pigs (13,57), and in primary kidney cultures (22), based on histological and morphological identification. This study confirmed the susceptibility of primary kidney epithelial cells to PCV2 infection using double immunofluorescence labeling of PCV2 antigens and cytokeratin, an epithelial-cell-specific intermediate filament.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a testis-derived epithelial-cell line (ST) was susceptible to PCV2 infection, showing that epithelial cells from other organs may also be susceptible to PCV2 infection. PCV2 infects epithelial cells in pigs experimentally infected with PCV2 (23), in PMWS pigs (13,57), and in primary kidney cultures (22), based on histological and morphological identification. This study confirmed the susceptibility of primary kidney epithelial cells to PCV2 infection using double immunofluorescence labeling of PCV2 antigens and cytokeratin, an epithelial-cell-specific intermediate filament.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo study reported that B cells may be the primary site of PCV2 replication during early infection (Yu et al, 2007), although in vitro studies have shown that PCV2 can replicate in primary porcine hepatocytes (Hirai et al, 2006) and that PCV2 particles can persist without replication in dendritic cells and porcine alveolar macrophages as well as in monocytes (Gilpin et al, 2003;Vincent et al, 2003). Thus, the target cells for PCV2 replication have not been clearly identified thus far.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of C. perfringens harboring netB gene in tissue sections was detected by ISH. The ISH was performed as described previously [ 6 ] with some modifications. Briefly, deparaffinized sections were treated with 0.2 N HCl at room temperature for 20 min and then digested with proteinase K (Sigma-Aldrich Japan Inc., Tokyo, Japan) at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were counterstained with Nuclear Fast Red (Roche Diagnostics GmbH) and systematically viewed under a light microscope. No background hybridization was seen when replicate tissue sections were incubated with an unrelated digoxigenin-labeled probe (PCV2-specific probe) [ 6 ] or when matched tissues from unaffected chickens were incubated with a netB gene-specific probe.…”
Section: Methodsmentioning
confidence: 99%